Fluidization treatment material and method for producing fluidization treatment material
By integrating carbon dioxide fixing particles from crushed ground improvement bodies and sludge into cement-based solidification materials, the method addresses the challenge of unstable compression strength and high emissions, achieving efficient recycling and reduced cement usage.
Patent Information
- Application Number
- JP2023120306
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
Smart Images

Figure 2025017262000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fluidized treatment material and a method for producing the fluidized treatment material. [Background technology]
[0002] Fluidized treated materials are used for backfilling and backfilling of foundations of structures, underground structures, and various urban lifelines. Conventionally, fluidization treatment materials have been used in the form of slurry obtained by dispersing a mixture of mud, waste soil, sludge, and sand (hereinafter also referred to as on-site generated soil) generated at construction sites, etc., with a cement-based or lime-based solidification material added, in water. One mode of use is the soil backfilling filling method, in which the slurry prepared by adding water and a solidification material to on-site generated soil generated at construction sites, etc., mixing and stirring is then performed, and the slurry is then injected into the site to backfill the site. From the viewpoint of effective utilization of waste, a technology has been proposed in which waste is mixed with incineration ash, molten slag, and other waste materials to produce fluidized treatment materials, thereby recycling the waste. Cement, a typical solidification component of fluidization treatment materials, emits a large amount of carbon dioxide due to its raw material and firing process for cement production, so there is a demand for reducing carbon dioxide emissions. One method is to use demolished concrete generated during the demolition of a structure as a concrete raw material. Fluidized materials obtained using cement as a solidification agent exhibit a desired strength by mixing and stirring an appropriate amount of cement as a solidification agent during production and hardening over time. However, simply reducing the amount of cement used can result in a decrease in the compressive strength of the resulting solidified material, or the composition of the soil generated on-site can fluctuate, resulting in an unstable compressive strength of the solidified material. In recent years, various uses of demolished concrete for the construction of buildings have been investigated, but there has been little attention paid to the application of demolished concrete to fluidized treatment materials.
[0003] Patent Document 1 describes a technique for expanding the uses of fine powder (also called recycled fine powder), which is generated as a by-product when producing recycled aggregate from concrete waste, by adding a small amount of the fine powder to cement clinker. Here, it is described that recycled fine powder is preferable from the viewpoint of improving the strength of the cement obtained by carbonating the cement to an advanced level, but the amount added is only about 5% by mass of the cement clinker, which is difficult to say that this is an efficient use of the recycled fine powder. Furthermore, Patent Document 2 focuses on fine powder obtained from waste concrete, discloses application of the fine powder to uses according to its carbonation, and proposes a method of recycling it as part of a cement raw material. The method described in Patent Document 1 describes a method of adding a small amount of fine waste concrete powder that is almost free of calcium hydroxide and has progressed carbonation to cement clinker, which is a cement raw material, and claims that it will be possible to expand the recycling of fine waste concrete powder.
[0004] Patent Document 2 proposes a technique for separating recycled fine aggregate and fine powder of waste concrete from waste concrete in consideration of the carbonation state of the waste concrete, and using them as recycled materials according to the carbonation state. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-254503 A [Patent Document 2] JP 2012-17227 A Summary of the Invention [Problem to be solved by the invention]
[0006] Recycling concrete waste generated by the demolition of concrete structures and other processes into cement is useful for reducing carbon dioxide emissions, but the methods described in Patent Documents 1 and 2 have the problem that they only achieve a small amount of recycling.
[0007] An object of one embodiment of the present disclosure is to provide a fluidized treatment material having good fluidity and uniaxial compressive strength of the solidified product. Another object of the present disclosure is to provide a suitable method for producing a fluidized treatment material. [Means for solving the problem]
[0008] Means for solving the above problem include the following aspects.
[0009] <1> A fluidization treatment material comprising at least one selected from the group consisting of carbon dioxide fixation particles, which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide fixation particles, which are a reaction product between carbon dioxide and crushed solidification material-containing sludge, a solidification material, and water. In the first embodiment of the fluidization treatment material, the particles obtained by crushing the ground improvement body rubble and the solidification material-containing sludge contain carbon dioxide gas immobilized particles in which carbon dioxide gas is immobilized, which gives the material good fluidity, and compared to conventional fluidization treatment materials, the compressive strength of the solidified product of the fluidization treatment material is improved even though the solidification material content is smaller. As a secondary effect, the method is promising for recycling waste materials that were previously difficult to recycle, such as ground improvement body debris and solidification material-containing sludge, and the amount of solidification material in the fluidization treatment material can be reduced. Furthermore, by including carbon dioxide gas immobilization particles in the fluidization treatment material, carbon dioxide gas can be immobilized in the fluidization treatment material.
[0010] <2> The crushed material of the ground improvement body debris and the crushed material of the solidification material-containing sludge contain soil material, and the maximum particle size of the carbon dioxide gas immobilization particles is 20 mm or less. <1> The fluidized treatment material described in. In the second aspect, the recycling applications of waste materials containing binders and soil particles such as soil, sand, etc., which have been difficult to recycle among conventional concrete waste materials, are expanded. By including carbon dioxide gas immobilizing particles, which are the reaction products of carbon dioxide gas and particles containing binders and soil particles such as soil, sand, etc., compared to the case where untreated waste materials are included, the fluidity is further improved, and furthermore, the compressive strength of the solidified product of the fluidization treatment material is improved.
[0011] <3> The content of the solidification material is 4.0% by mass to 20.0% by mass with respect to the total solid content of the fluidization treatment material. <1> or <2> The fluidized treatment material described in. In the third aspect, the content of the solidification material is kept low compared to conventional fluidization treatment materials, and sufficient compressive strength is achieved for the solidified material of the fluidization treatment material. Therefore, the content of cement, which is a typical solidification material, can be reduced, and the generation of carbon dioxide gas during cement production can be suppressed.
[0012] <4> The method for producing a fluidized treatment material includes the steps of: (I) crushing at least one selected from ground improvement body debris and solidification material-containing sludge to obtain a crushed material having a maximum particle size of 20 mm or less; (II) contacting the crushed material obtained in (I) with carbon dioxide to obtain carbon dioxide-immobilized particles; and (III) mixing at least one of the obtained carbon dioxide-immobilized particles with a solidification material and water to obtain a fluidized treatment material. In the fourth aspect, a fluidized treatment material having good fluidity and capable of providing a solidified product with sufficient compressive strength even when the content of the solidifying material is reduced can be suitably produced. In addition, by immobilizing carbon dioxide in particles that are at least one type of crushed material selected from ground improvement body debris and solidification material-containing sludge during production, the obtained carbon dioxide-immobilized particles become more brittle and are more likely to disintegrate when stirred and mixed during preparation of the fluidization treatment material, and as a result, the obtained fluidization treatment material has better fluidity. Furthermore, by including the carbon dioxide gas immobilizing particles, carbon dioxide gas can be immobilized in the fluidization treatment material, and emission of carbon dioxide into the atmosphere can be suppressed. Effect of the Invention
[0013] According to one embodiment of the present disclosure, a fluidized treatment material having good fluidity and uniaxial compressive strength of the solidified product can be provided. According to another aspect of the present disclosure, a suitable method for producing a fluidized treatment material can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The contents of the present disclosure will be described in detail below. These descriptions and examples are illustrative of the embodiments in the present disclosure and are not intended to limit the scope of the embodiments. In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.
[0015] In the present disclosure, the term "total solid content" refers to the total mass of the components excluding the solvent from the entire composition of the composition. Also, as described above, the term "solid content" refers to the components excluding the solvent, and the components may be solid or liquid at, for example, 25°C. "Room temperature" refers to an ambient temperature that is not specifically temperature controlled, and in this disclosure refers to "25°C" unless otherwise specified.
[0016] <Fluidization treatment material> The fluidization treatment material disclosed herein comprises at least one selected from the group consisting of carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed solidification material-containing sludge, a solidification material, and water.
[0017] In this disclosure, the "fluidization treatment material" refers to a composition containing at least one type of particle selected from the group consisting of carbon dioxide immobilizing particles, which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide immobilizing particles, which are a reaction product between carbon dioxide and crushed solidification material-containing sludge, a solidification material, and water. The fluidization treatment material is used in the form of a slurry by stirring and mixing the components contained in the composition. Examples of the method of using the fluidization treatment material include using it as a reinforcement material for the foundation of a structure, injecting it into holes after removing piles at a construction site, injecting it into backfilling sites after the completion of construction of various lifelines in cities, and using it as backfilling. The injected slurry-like fluidization treatment material hardens and provides the desired reinforcement at the backfill site, etc. Typically, fluidized treatment materials are made by adding solidification materials and water to on-site generated soil to form a slurry. However, as mentioned above, on-site generated soil has an inconsistent composition and contains soil particles of various particle sizes, making it poorly fluid and unstable in quality. Adding a large amount of water to ensure fluidity results in a problem of time-consuming hardening. In addition, increasing the content of the solidifying agent to improve the compressive strength of the solidified product results in problems such as a decrease in the effect of suppressing carbon dioxide generation.
[0018] The fluidization treatment material disclosed herein contains at least one type selected from the group consisting of carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed solidification material-containing sludge. Ground improvement soil, which has been difficult to recycle among on-site generated soil, and solidification material-containing sludge are made from waste materials containing soil particles and solidification materials such as cement. By crushing these waste materials and reacting them with carbon dioxide to produce carbon dioxide-immobilized particles, the resulting particles have a lower alkalinity and are more brittle due to carbonation than when crushed waste materials that do not immobilize carbon dioxide are used. Therefore, when the carbon dioxide gas fixing particles are stirred and mixed with the solidification material and water in preparation of the fluidized treatment material, the particles are decomposed and atomized due to their brittleness, which improves the dispersibility and fluidity of the mixture, and this good fluidity is maintained for a certain period of time even after the fluidized treatment material is prepared.
[0019] Below, each component contained in the fluidization treatment material of the present disclosure will be explained.
[0020] (Carbon dioxide gas immobilized particles) The fluidization treatment material disclosed herein contains at least one type selected from the group consisting of carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed solidification material-containing sludge. Hereinafter, the particles in which carbon dioxide gas has been immobilized, which are derived from crushed ground improvement body debris and crushed solidification material-containing sludge, may be collectively referred to as carbon dioxide gas immobilizing particles.
[0021] The ground improvement body gravel contains a solidification material such as concrete reinforced with a solidification material, and soil particles derived from the soil at the site. A slurry-like composition for forming the ground improvement body, which contains water and a solidification material, is injected into the soil at the site, and the mixture is stirred and mixed with the soil, hardening to form the ground improvement body. Therefore, the soil particles contained in the ground improvement body depend on the soil at the site, and may be, for example, sandy soil particles, clayey soil particles, or a mixture of these, and the particle size and properties of the soil particles themselves are not constant. Incidentally, "solidification material-containing sludge" is a general term for sludge in the form of a solidified material containing solidification materials such as soil cement and fluidized soil, and soil particles, and in a broad sense also includes ground improvement body debris. However, in this disclosure, since ground improvement body debris contains on-site generated soil as an essential component, for convenience, "ground improvement body debris" and "solidification material-containing sludge" are described separately.
[0022] Here, soil cement refers to a slurry prepared by mixing on-site generated soil with cement and water. The soil cement is transported to the site where it is to be used, and is spread and leveled with a bulldozer or backhoe, or compacted with a vibrating roller, etc., before being used, for example, as an internal component of a structure. Known fluidization treatment materials are slurry-like compositions that contain on-site soil, a solidification material such as cement, and water, and are used by pouring them into sites that require backfilling or backfilling. Hardened fluidization treatment materials are called fluidized treated soil.
[0023] The fluidization treatment material disclosed herein is prepared by reacting crushed material derived from ground improvement body debris and crushed material derived from solidification material-containing sludge with carbon dioxide to turn them into carbon dioxide-immobilized particles, which are used as the solid content of the fluidization treatment material.By using this as the solid content of the fluidization treatment material, the fluidization treatment material disclosed herein is not dependent on the components of the soil particles derived from the raw materials, and achieves good fluidity and high uniaxial compressive strength of the solidified material.
[0024] In the fluidization treatment material disclosed herein, it is preferable that the crushed ground improvement body debris and the crushed solidification material-containing sludge contain soil material, and that the maximum particle size of the carbon dioxide fixation particles is 20 mm or less. The maximum particle size of the carbon dioxide gas immobilizing particles can be confirmed by a sieving method, and the carbon dioxide gas immobilizing particles may be selected and used from those that pass through a sieve with 20 mm openings.
[0025] The carbon dioxide fixation particles (hereinafter also referred to as specific particles) contained in the fluidized treatment material of the present disclosure preferably have a carbon dioxide fixation amount of 30 kg or more per 1,000 kg of specific particles, more preferably 40 kg or more, and even more preferably 45 kg or more. By setting the amount of carbon dioxide gas adsorbed in the specific particles to 30 kg or more per 1,000 kg of specific particles, the fluidization treatment material disclosed herein can fix a large amount of carbon dioxide within its structure, thereby further reducing the burden on the environment.
[0026] The amount of carbon dioxide gas immobilized in the carbon dioxide gas immobilized particles can be determined from the mass loss at 600° C. to 800° C. in a TG-DTA test (Thermogrammetry-Differential Thermal Analysis). As a TG-DTA measuring device, for example, Thermoplus EVO2 TG-DTA8122 manufactured by Rigaku Corporation can be used. Here, the amount of calcium carbonate contained in the specific particles is measured, and the amount of carbon dioxide gas is calculated from the amount of calcium carbonate contained in the specific particles, and this is defined as the fixed amount of carbon dioxide gas (carbon dioxide content) in the specific particles.
[0027] The fact that specific particles become brittle and are subjected to the stress of stirring and mixing during the preparation of the fluidization treatment material, and are broken down into smaller particles, compared to crushed material derived from ground improvement body debris before reaction with carbon dioxide, and crushed material derived from solidification material-containing sludge, can be evaluated by mixing the particles and water in a specified mass ratio, classifying them through a 5 mm sieve, and measuring the mass of the particles remaining on the 5 mm sieve. Here, by using as particles the crushed material before it reacts with carbon dioxide and specific particles which are the reaction product of the crushed material with carbon dioxide and evaluating them under the same conditions, it is possible to confirm the state of embrittlement caused by the crushed material reacting with carbon dioxide. According to this evaluation, it is preferable that the mass of specific particles remaining on a 5 mm sieve is 50% by mass or less, more preferably 30% by mass or less, and even more preferably 10% by mass or less, of the crushed material that has not reacted with carbon dioxide gas. The evaluation results will be described in the Examples section below.
[0028] (Method of manufacturing carbon dioxide gas immobilized particles) By reacting crushed material derived from ground improvement body debris and crushed material derived from solidification material-containing sludge with carbon dioxide to obtain a reaction product, the carbon dioxide binds to the calcium contained in the solidification material in the crushed material, producing calcium carbonate (CaCO3), which makes it possible to fix carbon dioxide in the crushed material. First, a solidified material selected from ground improvement body rubble and solidification material-containing sludge is crushed to obtain a crushed material. Here, the maximum particle size of the crushed material before reacting with carbon dioxide is preferably 40 mm or less, more preferably 30 mm or less, and even more preferably 20 mm or less. The crushed material is a solidified material that contains at least soil particles derived from on-site generated soil and a solidification material. The crushed material is reacted with carbon dioxide gas to immobilize the carbon dioxide gas in the crushed material, thereby forming carbon dioxide-immobilized particles containing calcium carbonate. The reaction between the carbon dioxide gas and the crushed material may be carried out by either a dry method or a wet method. The reaction conditions between carbon dioxide gas and crushed material will be described in detail in the section on the manufacturing method of fluidized treatment material.
[0029] There are no particular limitations on the specific particles, so long as they are particles that can pass through a sieve with 20 mm openings and have a maximum particle size of 20 mm or less. For example, the crushed material obtained by crushing ground improvement body debris or solidification material-containing sludge is preferably crushed material having a maximum particle size of 50 mm or less, more preferably crushed material having a maximum particle size of 30 mm or less, and even more preferably crushed material having a maximum particle size of 20 mm or less. By reacting the crushed material having the above maximum particle size with carbon dioxide gas, the reaction with carbon dioxide gas proceeds quickly, making it easier to obtain specific particles having a maximum particle size of 20 mm or less, which is a preferred embodiment. As long as the maximum particle size of the specific particles is the preferred 20 mm or less, there are no particular restrictions on the particle size distribution, etc., that may be affected by differences in the crushing method used to crush the ground improvement body debris or solidification material-containing sludge in producing the crushed material. From the viewpoint of the balance between the amount of carbon dioxide gas fixed, the fluidity of the resulting fluidized treatment material, and the strength of the solidified fluidized treatment material, the average particle size of the specific particles is preferably 30 mm or less, more preferably 20 mm or less, even more preferably 10 mm or less, and most preferably 5 mm or less. In the present disclosure, by using waste materials, such as ground improvement body debris and solidification material-containing sludge, as the raw materials for the specific particles contained in the fluidization treatment material, it becomes possible to recycle the above-mentioned waste materials and reduce the amount of new concrete-derived solidification material added to the fluidization treatment material in order to make the uniaxial compressive strength of the solidified product of the resulting fluidization treatment material at a level that is acceptable for practical use.Furthermore, it is believed that by using the specific particles, carbon dioxide gas is fixed in the fluidization treatment material, thereby further reducing carbon dioxide gas emissions.
[0030] The content of the specific particles contained in the fluidization treatment material can be 70% by mass to 80% by mass, preferably 80% by mass to 90% by mass, and more preferably 90% by mass to 100% by mass, of the total solid content of the fluidization treatment material.
[0031] (Solidification material) The fluidization treatment material of the present disclosure includes a solidification material. As the solidification material, any known hydraulic component can be used without limitation. As the solidification material, cement, specifically, Portland cement, blast furnace cement type B, blast furnace cement type C, cement-based solidification material, etc., which are used in ordinary fluidization treatment materials, can be used, and cement, especially Portland cement, is preferred. The fluidized treatment material disclosed herein contains at least one of the modified powders and modified fine aggregates described above, so that even if the amount of solidification material used in the fluidized treatment material is reduced, the compressive strength of the final solidified product can be maintained within a range that does not cause practical problems. The content of the solidification material is preferably 4.0 mass % to 20.0 mass %, more preferably 4.2 mass % to 19.7 mass %, and even more preferably 5.0 mass % to 15.0 mass %, based on the total solid content of the fluidization treatment material.
[0032] (water) The fluidization treatment material of the present disclosure includes water. There are no particular limitations on the water contained in the fluidization treatment material. When preparing a slurry-like composition that can be mixed with the above-mentioned modified powder and solidifying agent to be injected as a fluidization treatment material, as long as it satisfies conditions such as not containing any harmful substances and not impairing the hardening properties of the binder, tap water, reclaimed water, stored rainwater, etc. may be appropriately selected and included. The water content is appropriately selected depending on the objectives, such as the fluidity required for the fluidization treatment material and the compressive strength of the solidified product. The total content of solids contained in the fluidization treatment material, such as binder and modified powder, relative to the mass of water, i.e., the water / solid ratio, can be 25% to 150%. Note that, when the water / solid ratio is set to, for example, 60% or less for the purpose of improving the compressive strength of the solidified fluidization treatment material, a known chemical admixture may be further included for the purpose of improving fluidity.
[0033] There are no particular limitations on the method of using the fluidization treatment material disclosed herein, and it can be applied to general methods of use, such as soil backfilling and filling methods, and pile extraction hole backfilling methods, and the fluidization treatment material can be made into a slurry and injected for use. The fluidized treatment material disclosed herein contains at least one of modified powder and modified fine aggregate derived from recycled concrete debris, and therefore has good fluidity and good compressive strength of the solidified product, making it suitable for a variety of applications. In addition, since carbon dioxide gas is fixed in the modified powder and modified fine aggregate contained in the fluidized treatment material, the fluidized treatment material has the additional effect of fixing carbon dioxide gas in the backfill material, such as the ground, which is useful for reducing carbon dioxide gas in the atmosphere.
[0034] There are no particular limitations on the method for producing the fluidized treatment material of the present disclosure, but from the standpoint of effectiveness, it is preferable to produce it by the method for producing the fluidized treatment material of the present disclosure described below.
[0035] <Method of manufacturing fluidized treatment material> The manufacturing method of the fluidized treatment material disclosed herein (hereinafter also referred to as the manufacturing method disclosed herein) includes step I of pulverizing at least one selected from ground improvement body debris and solidification material-containing sludge to obtain a pulverized material having a maximum particle size of 20 mm or less, step II of contacting the pulverized material obtained in step I with carbon dioxide to obtain carbon dioxide-immobilized particles, and step III of mixing at least one of the obtained carbon dioxide-immobilized particles with a solidification material and water to obtain a fluidized treatment material.
[0036] (Process I) Step I is a step of pulverizing at least one selected from ground improvement body debris and solidification material-containing sludge to obtain a pulverized material having a maximum particle size of 20 mm or less. There are no particular limitations on the method for crushing or grinding at least one type selected from ground improvement body debris and solidification material-containing sludge to obtain pulverized material with a maximum particle size of 20 mm or less, and any known crushing or grinding device can be used. At least one selected from the group consisting of ground improvement body debris and solidification material-containing sludge may first be coarsely pulverized, and the resulting coarsely pulverized material may then be further crushed or ground, thereby carrying out multi-stage crushing or the like. For the coarse crushing of at least one selected from the ground improvement body debris and the solidification material-containing sludge, a known crusher such as a jaw crusher or an impeller breaker can be used. When the coarsely pulverized material is further subjected to crushing or the like, for example, a crushing device of the blast shot type, an impact crusher, or a grinding device of the mechanical rubbing type without heating can be used.
[0037] At least one material selected from ground improvement body debris and solidification material-containing sludge is crushed or ground to obtain coarsely crushed material having a particle size of 40 mm or less, which is then further crushed or ground, and the crushed material is then classified by particle size to obtain crushed material having a maximum particle size of 20 mm or less. Methods for further crushing concrete blocks with a particle size of 40 mm or less include crushing using a crusher such as a jaw crusher or impeller breaker, using a mechanical grinding method that does not involve heating, using a heated grinding method, and the blast shot method. From the viewpoint of less energy consumption, crushing using a crusher, the mechanical grinding method that does not involve heating, and the blast shot method are preferred.
[0038] The pulverized product may be obtained having a maximum particle size of 20 mm or less by a known method, such as sieving.
[0039] (Process II) Step II is a step of contacting the pulverized product having a maximum particle size of 20 mm or less obtained in step I with carbon dioxide gas to obtain carbon dioxide-immobilized particles (specific particles) in which carbon dioxide gas is immobilized. The reaction between the ground material and carbon dioxide gas may be a dry method or a wet method. As a dry method, the reaction between the crushed material and carbon dioxide gas can be carried out by placing the crushed material in a closed space and contacting it with carbon dioxide gas having a concentration of 5% or more in an atmosphere having a temperature of 5°C to 200°C. As a wet method, the crushed material is immersed in water and carbon dioxide gas is supplied to the water until the pH of the water reaches 6 to 8.
[0040] (Reaction of crushed material with carbon dioxide: dry method) When the reaction between the crushed material and carbon dioxide gas is carried out by a dry method, the crushed material is placed in a closed space, and the closed space is filled with carbon dioxide gas at a concentration of 5% or more to bring the crushed material into contact with the carbon dioxide gas, thereby obtaining specific particles.
[0041] In step II, carbon dioxide gas separated and recovered in a factory or the like can also be used as carbon dioxide gas for the reaction. By using exhaust gas containing carbon dioxide, recovered carbon dioxide, etc. for the carbonation process, it is possible to simultaneously reduce the amount of carbon dioxide in the exhaust gas and modify the crushed material by adsorption of the carbon dioxide to the crushed material. When the temperature of the exhaust gas is high, exceeding 100°C, efficient carbonation can be performed without particularly heating the closed space, and there is also the advantage that reduction in energy consumption and reduction in carbon dioxide in the exhaust gas can be achieved at the same time. In order to efficiently carbonate the crushed material, the closed space may be pressurized and carbon dioxide gas may be supplied to contact the crushed material. The dry treatment can also be carried out using a commercially available neutralization accelerator (for example, a high-concentration neutralization accelerator test device manufactured by Marui Co., Ltd.).
[0042] The preferred treatment time in the dry method is appropriately selected in relation to the carbon dioxide gas concentration and supply amount. For example, when carbon dioxide gas with a concentration of 10% to 50% is used, the treatment time can be 1 hour or more, preferably 24 hours or more, more preferably 2 days or more, even more preferably 5 days or more, and even more preferably 10 days or more. There is no particular upper limit to the treatment time, but from the viewpoint of production efficiency, it can be 20 days or less. The preferred treatment time can be appropriately selected depending on the state of the crushed material and the required physical properties of the specific particles. For example, the soil contained in the crushed material can vary depending on the soil quality at the site, and can be clayey soil containing fine soil particles such as clay, sandy soil containing larger soil particles than clayey soil, or a mixture of clayey soil and sandy soil. It is preferable for the fluidized treatment material to contain clayey soil that is brittle and easily collapses after reaction with carbon dioxide gas, in view of further improving the fluidity of the fluidized treatment material.
[0043] In the case of the dry method, the reaction time with carbon dioxide gas can be 1 hour or more. In addition, when the treatment time in the dry method is 5 days or more, from the viewpoint of making the carbonation progress more efficient, it is preferable to stir the crushed material left in the closed space about once every several hours to 3 days. Stirring allows the crushed material to come into contact with carbon dioxide more uniformly, so that the crushed material is carbonated entirely and the unreacted areas where the carbon dioxide does not react can be reduced.
[0044] (Reaction of crushed material with carbon dioxide: wet method) The wet method can be carried out by immersing the crushed material obtained in step I in water and supplying carbon dioxide gas to the water until the pH of the water reaches about 6 to 8, preferably 6.8 to 8.0, and more preferably about 6.8 to 7.0. A specific example of the wet method is to immerse the crushed material in water by placing it in a container and filling it with water, then injecting carbon dioxide gas into the water to create bubbles. By immersing the crushed material in water, the pH of the immersion liquid may become about 10 to 12 due to the effect of the solidification material contained in the crushed material. For example, a method can be adopted in which the crushed material is mixed with water, then left to stand for 30 to 90 minutes to allow the crushed material to blend with the water, and then carbon dioxide gas is supplied to the water.
[0045] There is no particular limitation on the water used for immersion. From the viewpoint of treatment efficiency, it is preferable that the water used contains a small amount of impurities that form salts upon contact with carbon dioxide gas, and examples of the water that can be used include tap water, industrial water, and ion-exchanged water.
[0046] When the wet method is carried out, the carbon dioxide gas concentration supplied to the water can be 5%, preferably 10% or more, and more preferably 20% or more. There is no particular upper limit to the carbon dioxide gas concentration, and the carbon dioxide gas concentration may be 100%. The higher the carbon dioxide concentration, the better the carbonation efficiency of the regenerated powder and the like tends to be. The carbon dioxide gas to be supplied may be exhaust gas containing carbon dioxide gas, recovered carbon dioxide gas, etc., as in the dry method. When exhaust gas, etc. is used as a carbon dioxide gas supply source, the carbon dioxide gas concentration depends on the amount of carbon dioxide gas contained in the exhaust gas. Even when exhaust gas is used, the carbon dioxide gas concentration in the exhaust gas is preferably 5% or more.
[0047] The amount of carbon dioxide gas supplied to the water in which the crushed material was immersed was set at a supply rate of 1 m 3 / hr~100m 3 By blowing in carbon dioxide gas at the above-mentioned supply rate, the crushed material immersed in water is sufficiently contacted with the carbon dioxide gas, and the crushed material and the carbon dioxide gas react sufficiently to obtain specific particles.
[0048] The amount of carbon dioxide gas supplied to the water in which the crushed material is soaked and the supply rate of carbon dioxide gas at the above concentration can be appropriately selected depending on the purpose. By blowing carbon dioxide gas with the supply amount (total amount) and supply rate of carbon dioxide gas optimized, the crushed material soaked in water comes into contact with the carbon dioxide gas efficiently, and the reaction between the crushed material and the carbon dioxide gas proceeds. In addition, the solubility of carbon dioxide in water increases as the water temperature decreases, so there is no need to specifically control the water temperature. When exhaust gas is used as a carbon dioxide supply source, the water temperature may rise depending on the temperature of the exhaust gas. However, since the water temperature never reaches 100°C, it is not expected to affect the reaction between the crushed material and carbon dioxide.
[0049] There is no particular restriction on the temperature of water in the wet method, and the method can be carried out at room temperature. When exhaust gas is used to supply carbon dioxide, the temperature of the water may rise to, for example, about 90°C depending on the temperature and amount of exhaust gas supplied, but the reaction between the crushed material and carbon dioxide proceeds even under such temperature conditions.
[0050] There is no particular limitation on the treatment time for supplying carbon dioxide gas in the wet method. The reaction time in the wet method can be, for example, 5 minutes to 10 hours, and is preferably 30 minutes to 6 hours. Since the pH of the water tends to decrease as the carbonation of solidification material-derived components such as cement contained in the crushed material progresses due to contact between the crushed material and carbon dioxide gas, the end point of the carbonation treatment may be the time when the pH of the water reaches 6 to 8. It is preferable to carry out the wet treatment until the pH of the water reaches 6.5 to 7.0, and it is more preferable to carry out the wet treatment until the pH reaches 6.5 to 6.8. It is even more preferable to continue the wet treatment for an additional 30 to 90 minutes after the pH of the water reaches a target value, for example, the pH of the water reaches 6.5 to 7.0. It is also more preferable that once the pH reaches the desired value, the wet treatment is continued for an additional 30 to 90 minutes, and then the water is allowed to stand for an additional hour, after which it is confirmed that the change in pH of the water is 0.2 or less, marking this as the end point of the carbonation treatment. The pH of the water in the wet process can be measured with a known pH meter.
[0051] (Process III) Step III is a step of obtaining a fluidization treatment material by mixing the specific particles obtained in step II with a solidification material and water. The fluidization treatment material is generally prepared on-site. First, the specific particles and the solidification material obtained in step II are weighed, added to a predetermined amount of water, and thoroughly stirred and mixed to obtain a slurry-like fluidization treatment material. The fluidization treatment material of the present disclosure contains specific particles, and the specific particles embrittled by reaction with carbon dioxide gas are decomposed into particles with smaller particle diameters by the stress during stirring and mixing, and the number of particles with even smaller particle diameters than the crushed material increases. Therefore, compared to the case where the fluidization treatment material contains particles that are crushed material before reacting with carbon dioxide gas, the fluidity is better due to the smaller particle diameter of the specific particles, and the fluidization treatment material shows injectable fluidity both immediately after preparation and after 60 minutes have passed since preparation.
[0052] In step III, when the prepared fluidization treatment material is charged at the site while maintaining its fluidity, the water / solids ratio can be 50% to 300%. In addition, when the water / solid ratio is set to 60% or less, preferably in the range of 47% to 55%, for the purpose of improving strength, etc., it is preferable to use a chemical admixture from the viewpoint of improving fluidity. That is, the fluidization treatment material prepared in step III can further contain a chemical admixture.
[0053] The chemical admixture may be selected from known chemical admixtures capable of improving the fluidity of the cement slurry, and examples of the chemical admixture include chemical admixtures containing a water-soluble vinyl copolymer. The content of the chemical admixture is appropriately selected depending on the purpose, and is generally, but not limited to, 0.3 mass % to 1.0 mass % based on the total mass of the binder.
[0054] (Application method for fluidized treatment materials) Next, a method for applying a fluidized treatment material using the mixture obtained by the manufacturing method of the present disclosure will be described below. Hereinafter, an example will be described in which cement is used as a binder. The fluidized treatment material is poured into the space to be backfilled while maintaining its fluidity. The fluidized treatment material obtained by the manufacturing method of the present disclosure has good fluidity and stability over time, and therefore maintains a favorable fluidity for about one hour after preparation, making it suitable for use in various sites.
[0055] The fluidized treatment material disclosed herein has good fluidity and the compressive strength of the solidified material is at a level that does not pose any practical problems, and therefore can be suitably used in any construction method, forming the necessary solidified material and making it suitable for backfilling, etc. According to the manufacturing method of the fluidized treatment material disclosed herein, the content of binder such as cement used in the manufacture of the fluidized treatment material is reduced, and modified powder in which carbon dioxide gas is immobilized is used. As a result, a uniaxial compressive strength is achieved that is sufficient for practical use, the necessary reinforcing effect is obtained, and because it contains a dense modified powder in which carbon dioxide gas is fixed, it is expected that the leakage of harmful substances at construction sites, for example, can be suppressed.
[0056] The fluidized treatment material disclosed herein can be directly applied to any of the construction methods for conventional fluidized treatment materials, and one of the advantages of the manufacturing method disclosed herein is that the solidified material in which carbon dioxide is easily immobilized is immobilized, for example, in the ground, thereby reducing the release of carbon dioxide into the atmosphere. In addition, the use of modified powders derived from recycled concrete debris can also lead to the effective use of waste materials, including concrete.
[0057] (Physical properties of solidified fluidized treatment materials) -Compressive strength- The solidified fluidized treatment material of the present disclosure preferably has a compressive strength that is practically acceptable for the intended purpose. The strength development of the solidified material of the fluidized treatment material is judged by the uniaxial compressive strength of the solidified material measured by the following method. Unconfined compressive strength is measured based on JIS A 1108:2018. The target value of the uniaxial compressive strength of the solidified material of the fluidized treatment material disclosed in this disclosure is appropriately selected depending on the purpose of construction, but generally, the uniaxial compressive strength of the solidified material at 7 days is 0.1 N / mm 2 The unconfined compressive strength of the solidified material after 30 days is 0.2N / mm 2 More preferably, it is equal to or greater than this.
[0058] -pH of fluidized material- Since the fluidized treatment material of the present disclosure contains modified powder in which carbon dioxide gas is immobilized, the alkalinity is reduced compared to when it contains regenerated powder in which carbon dioxide gas is not immobilized. As a guideline, the pH of the fluidized material at one day of age is preferably 12.0 or less. The pH of the fluidized material containing recycled powder, etc., measured at one day of age is about 12.35, which is expected to reduce the alkalinity and, for example, reduce the impact of alkalinity on nearby metal components.
[0059] -Liquidity- From the viewpoint of workability, it is preferable that the fluidization treatment material has good fluidity. The fluidity of the fluidized treatment material is measured in terms of flow value in accordance with JIS R 5201. The flow value one hour after the preparation of the fluidized treatment material is preferably 140 mm or more, and more preferably 200 mm or more. Bleeding is evaluated in accordance with the Japan Society of Civil Engineers standard "Test method for fluidity of injection mortar for prepacked concrete (JSCE-F 522-2018)." Bleeding is preferably 1.0% to 3.0% after 24 hours, and more preferably less than 1.0%.
[0060] - Changes in particle size of specific particles - The specific particles obtained through the step II have a smaller maximum particle size due to the stress during stirring and mixing, compared to the crushed material before the reaction with carbon dioxide gas. The change in particle size of specific particles can be evaluated using the method described above. Compared to untreated crushed material, it is preferable that the number of particles passing through a sieve with 5 mm openings increases by 50% by mass or more, and more preferably by 70% by mass or more. EXAMPLES
[0061] The fluidized treatment material and the manufacturing method thereof according to the present disclosure will be described below with reference to examples. It goes without saying that the fluidized treatment material and the manufacturing method thereof according to the present disclosure are not limited to the following examples, and various modifications are included within the scope of the present disclosure.
[0062] <Specific Particle Manufacturing Example 1 and Manufacturing Example 2> The specific particles were produced using the following crushed ground improvement body and crushed solidification material-containing sludge as raw materials. The crushed material of the ground improvement body includes sandy soil. The pulverized solidification material-containing sludge contains clayey soil.
[0063] The crushed ground improvement body and the crushed solidification material-containing sludge were collected at the demolition site, crushed with a jaw crusher, and sieved to obtain crushed material with a maximum particle size of 20 mm or less. (Step I)
[0064] Each of the crushed materials obtained was placed in a neutralization promotion device (high-concentration neutralization promotion test device manufactured by Marui Co., Ltd.) and carbon dioxide gas was injected into the device, causing the crushed materials to react with the carbon dioxide gas to obtain specific particles. First, a neutralization accelerator equipped with a 20 L container was prepared, the crushed material was evenly laid out in the container, and the environment inside the container was set to a carbon dioxide concentration of 10%, a temperature of 20±2°C, and a humidity of 60±5%RH. The crushed material was left stationary and contacted with carbon dioxide, and was stirred every 2-3 days to distribute evenly. This was continued for 7 days to obtain specific particles. The specific particles obtained using the crushed material containing clayey soil were designated as specific particles (I), and the specific particles obtained using the crushed material containing sandy soil were designated as specific particles (II).
[0065] (Evaluation of carbon dioxide fixation powder) The specific particles (I) and specific particles (II) obtained through step II were evaluated for physical properties by the following methods.
[0066] In the TG-DTA test, the amount of calcium carbonate in each powder was calculated from the mass loss at 600℃ to 800℃ using Thermo plus Evo2 TG-DTA8122 (manufactured by Rigaku Corporation). Furthermore, the amount of carbon dioxide fixed in the powder was calculated from the amount of calcium carbonate. As a result, the amount of carbon dioxide fixed in specific particle (I) was 77.6 CO2-kg / m 3 The amount of carbon dioxide fixed in the specific particle (II) is 77.6 CO2-kg / m 3 It was.
[0067] (Evaluation of brittleness of specific particles) The specific particles (I) and (II) were used to improve brittleness, and the micronization caused by the stress of stirring and mixing was evaluated according to the following criteria. First, 6.5 kg of the specific particles were prepared, and the specific particles and water were mixed in a ratio of 26:74 by mass to obtain a fluidized treatment material for evaluation. The obtained fluidized treatment material was classified using a sieve with 5 mm openings, and the mass of the particles remaining on the sieve with 5 mm openings was measured. As a control example, the crushed material before reacting with carbon dioxide and water were mixed in a ratio of 26:74 by mass, and a comparative fluidized treatment material was prepared under the same conditions as above and evaluated in the same manner.
[0068] As a result, for the crushed material containing clayey soil, the mass of the particles of specific particle (I) remaining on a sieve with a mesh size of 5 mm was 40.5 g, and for the unreacted crushed material, it was 2543.2 g. That is, 60.9% by mass of the unreacted crushed material passed through a sieve with 5 mm openings, whereas 99.4% by mass of the specific particles (I) passed through a sieve with 5 mm openings. This shows that, for specific particles (I), the proportion of particles with a small maximum particle size during preparation of the fluidization treatment material is significantly increased compared to untreated crushed material, improving the fluidity of the fluidization treatment material.
[0069] Next, specific particles (II) derived from crushed material containing sandy soil were evaluated. Specific particles (II) were evaluated in the same manner as specific particles (I), except that the ratio of specific particles to water was 46:54.
[0070] As a result, in the crushed material containing clayey soil, the mass of the particles of specific particle (II) remaining on a sieve with a mesh size of 5 mm was only 7.22 g, while in the case of the unreacted crushed material, it was 642.1 g. That is, 90.1% by mass of the unreacted crushed material passed through a sieve with a mesh size of 5 mm, whereas 99.9% by mass of the specific particles (II) passed through a sieve with a mesh size of 5 mm. From this, it can be seen that even when the material contains sandy soil that is easily dispersed, the maximum particle size of the specific particles (II) becomes smaller during preparation of the fluidized treatment material, and the fluidity of the fluidized treatment material is improved compared to that of untreated crushed material.
[0071] <Examples 1 to 4> The obtained specific particles (I) and specific particles (II) were used to produce a fluidization treatment material. Tap water was used for the production of the fluidization treatment material. (Materials used) -Binding material- Portland cement (Nippon Steel Blast Furnace Cement Co., Ltd., density: 3.02 g / cm 3 )
[0072] - Carbon dioxide gas immobilization particles - Specific particles (I) and specific particles (II) obtained in the above manufacturing examples
[0073] The specific particles (I), specific particles (II), cement (solidification material), and water were mixed in the amounts shown in Table 1 below, and stirred to produce the fluidization treatment materials of Examples 1 to 4. (Step III) The mixture was thoroughly mixed and stirred, and the flow value and bleeding were measured according to the methods described above, and evaluated according to the following evaluation criteria.
[0074] (Flow value) A: Over 200mm B: 140mm~200mm C: Less than 140mm The ratings A and B are at levels that pose no practical problems.
[0075] (Breeding) A: Less than 1.0% B: 1.0% to 3.0% C: More than 3.0% The ratings A and B are at levels that pose no practical problems.
[0076] (Compressive strength of solidified material) The produced fluidized treatment material slurry was poured into a formwork (size: diameter 50 mm, height 100 mm) and allowed to harden to obtain a solidified material for uniaxial compression tests. The compressive strength was measured using the method described above and evaluated according to the following criteria. -Unconfined compressive strength at 3 days old- A: 0.05N / m 2 Exceed B: 0.03N / m 2 ~0.05N / m 2 C: 0.03N / m 2 less than
[0077] - Uniaxial compressive strength at 7 days old - A: 0.1N / m 2 Exceed B: 0.065N / m 2 ~0.1N / m 2 C: 0.065N / m 2 less than The results are shown in Table 1.
[0078] (Alkalinity rating) The alkalinity of the obtained fluidization treatment materials of Examples 1 to 4 at an age of 7 days was evaluated by measuring the pH. The results are shown in Table 1. In addition, the pH of the fluidized treatment material prepared in the same manner using carbon dioxide and unreacted crushed material was 12.29 for the crushed material containing clayey soil, and 12.30 for the crushed material containing sandy soil, showing almost no change from the pH of 12.40 immediately after preparation.
[0079] (Carbon dioxide emissions) Carbon dioxide emissions were calculated by subtracting the amount of carbon dioxide fixed in the hardened material of the fluidization treatment material from the amount of carbon dioxide generated during the production of cement, which is used as a solidification material in the production of each fluidization treatment material. Carbon dioxide emissions resulting from the energy used in transporting materials and applying the fluidization treatment materials are not taken into account. The carbon dioxide generated during cement production was calculated using the value of 451.8 kg-CO2 / t for blast-furnace cement type B in the appendix on page 8 of the Cement Association: Summary of Cement LCI Data (February 2023). (See https: / / www.jcassoc.or.jp / cement / 4pdf / jg1i_01.pdf) The amount of carbon dioxide fixed in the solidified fluidized treatment material was calculated assuming that the amount of carbon dioxide fixed per 1,000 kg of specific particles is 77.6 kg-CO2 / t. In Table 1, carbon dioxide emissions are listed as "CO2 emissions."
[0080] [Table 1]
[0081] As can be seen from the results in Table 1, the fluidized treatment materials of the examples containing specific particles (I) and specific particles (II) all had good fluidity, and the uniaxial compressive strength of the solidified material was at a level that did not pose any practical problems. The fluidization treatment material contains modified powder with carbon dioxide gas immobilized therein, and thus has the effect of reducing the amount of carbon dioxide gas released into the atmosphere during production. That is, the amount of carbon dioxide emitted during the production of the solidification material alone used in the examples was calculated to be 67.5 kg-CO2 / t, and compared with this value, it can be seen that the amount of carbon dioxide emitted during the production of the fluidization treatment materials of Examples 1 to 4 is significantly reduced compared to the production of the solidification material alone. In addition, since the alkalinity of the fluidized treatment material is reduced, it is expected that the impact of alkalinity on metal materials at the site of use will also be reduced.
Claims
1. A fluidization treatment material comprising at least one selected from the group consisting of carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed ground improvement body debris, and carbon dioxide fixation particles which are a reaction product between carbon dioxide and crushed solidification material-containing sludge, a solidification material, and water.
2. The fluidization treatment material according to claim 1, wherein the crushed ground improvement body debris and the crushed solidification material-containing sludge contain soil material, and the maximum particle size of the carbon dioxide fixation particles is 20 mm or less.
3. The fluidization treatment material according to claim 1 or 2, wherein the content of the solidification material is 4.0% by mass to 20.0% by mass based on the total solid content of the fluidization treatment material.
4. A step I of crushing at least one selected from ground improvement body debris and solidification material-containing sludge to obtain a crushed material having a maximum particle size of 20 mm or less; A step II of contacting the crushed material obtained in the step I with carbon dioxide gas to obtain carbon dioxide gas-immobilized particles; A method for producing a fluidized treatment material, comprising step III of mixing at least one of the obtained carbon dioxide gas immobilized particles with a solidification material and water to obtain a fluidized treatment material.
Citation Information
Patent Citations
Fine powder cement
JP2010254503A
Waste concrete fine powder and method for recovering the same
JP2012017227A